Peripheral precocious puberty due to congenital adrenal hyperplasia with vanishing testis: a rare case in radiology - Indira Prawita Martani; Pande Putu Yuli Anandasari; Dewa Gde Mahiswara Sudiatmika (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2020)
Background: Genetically, peripheral precocious puberty can be caused by congenital adrenal hyperplasia (CAH). Radiological examination is used for etiology findings and diagnostics. Peripheral precocious puberty of CAH generally affects girls with genitalia disambiguate, less common in boys. Incidence is I in 15.000 to 20.000 children with a female to male ratio of about 20:1. Case Report: A 5-year-old boy with voice change and hair growth in his penis. An immunoserology, endocrinology, electrolyte laboratory examination had been performed. Besides, some radiological tests of diagnostic bone age, upper abdominal ultrasound, and testicular ultrasound had been determined as confirmation of laboratory findings that support peripheral precocious puberty. In this case, an examination of human skeletal maturity was obtained according to the age of 14. Ultrasound examination showed adrenal enlargement with a size of 4 x 0.6 cm with a V-shaped and cribriform appearance. No testicular was found in the scrotum or the inguinal canal. Both 17-hydroxyprogesterone and testosterone level was increased subsequently. Conclusion: Bone age examination is needed to determine skeletal maturity. An ultrasound can be used to determine both etiology and concomitant abnormalities of the genital system. However, ultrasound can not detect the location of the testicle intraperitoneally. MRI examination is an imaging technique that is recommended if no testicles are found in the scrotum or inguinal.